Modifying Greima's structural semantics for poetry analysis - Bacabac, Florence Elizabeth (1997)
Greima's notion that a text has "structural unity" where elements are grasped as functions of a dynamic whole is the basis of his Structural Semantics which provides a structural ground for linguistic analysis of poetry. Here, analysis starts from a linguistic level but does not necessarily end in that level. Culled from a master's thesis, this paper highlights the structuring activity of the reader.
Keywords: Poetry -- Appreciation and Interpretations